Use of powdered and liquid polymers including pre- packaged Polymer Modified Mortar in Concrete technology in Pakistan: Types Being Used, Application Areas, Market Size, Cost Trends and Future Prospects - Hunzala Fatima; Sohail Anwar; Musarrat Ullah Khan Afridi; Zeeshan Ullah (`, 2026)
Purpose: This study sees into the adoption of polymer modified concrete in Pakistan through evaluating types of polymers used, applications of polymer concrete, coverage in the market, changes in the cost of polymer concrete and future prospects, construction industry. While the incorporation of polymer is well known around the world for its beneficial effect on performance and durability of concrete, there is little globally available industry level evidence for the development of construction markets like that of Pakistan. The purpose of the study is to make a comprehensive technical and market oriented survey on the aspects of utilization of polymer in Pakistan. Design/Methodology/Approach: A structured questionnaire survey was carried out amongst these participants which comprised of 367 construction professionals such as engineers, contractors, consultants and material suppliers. Responses were formatted through a Likert scale methodology and were analyzed through descriptive statistical methods to assess usage trends, performance perceptions and market barriers. Findings: Results show that 68% of the respondents do regular use of superplasticizer-based polymer with polycarboxylate ether (PCE) being the dominant type with mean score passage >3.8/5. Some 61% of professionals were have associated the use of polymers with the improvement of workability; 54% with the improved development of strength. Durability advantages of lower permeability and longer service life were accepted by more than three quarters of the participants. Polymer latexes and fibers thus have been more frequently used in the repair and waterproofing works than in the mass concrete. However, 72% of the respondents mentioned high cost and 65% of them reported import dependency as major barriers that limit wider adoption. Trends in the market have been slow and gradual growth due to high rise projects, infrastructure projects Implications/Originality/Value: The study provides one of first industry-wide empirical assessment of polymer used in concrete in Pakistan through technical performance perceptions along with market realities in Pakistan. Findings include the need for local manufacturing, industry training and supportive policy frameworks for better adoption. The results offer an evidence-based advice to engineers, material producers, researcher as well as policymakers who wish to promote durable and performance-oriented concreting models in emerging construction markets. Keywords: Polymer-modified concrete; Superplasticizers; Concrete durability; Polymer admixtures; Construction materials; Market adoption; Sustainable construction; Pakistan construction industry.